Mission Thrombectomy 2020 (MT2020)—India's Biggest Healthcare Challenge Yet. Issue 2 (December 2020) - Sundar, Kaushik; Panwar, Ajay; Yagaval, Dileep R.; Huded, Vikram; Sylaja, P.N.
Large vessel occlusion has a disproportionately large contribution to overall mortality and morbidity from stroke. The Society of Vascular and Interventional Neurology in the year 2016 announced the launch of Mission Thrombectomy 2020 (MT2020), with the aim of increasing access to stroke thrombectomy globally. Despite 4 years since the start of MT2020, India is falling short in acute stroke therapy including thrombolysis and mechanical thrombectomy (MT). Access to timely MT leads to substantial mitigation of adverse stroke outcomes. This in turn leads to an enormous health benefit in that population. MT as a treatment is unevenly and unfairly distributed and increasing access to it is in need of strategies targeting political, economic, and environmental factors. Such strategies are slowly being adopted. In this article, we attempt to look at the major hurdles we face in improving acute stroke care in our country and we also explore options to address them.